Propuesta de manual de clasificación de puestos, valuación de puestos por puntos y reglamentos de admisión y empleo para la empresa EQFALTO de la ciudad de Quito - Calva Castillo, Gina Elizabeth (2014)
This thesis was developed with the goal of "Developing the manual job classification, job evaluation points and the rules of admission and employment for the company EQFALTO" for this deductive, inductive, analytic and synthetic methods were used, which permitted a orderly and systematic study based on information obtained through investigative, such as observation, survey of 41 employees and interview the manager of the entity under study techniques. In the literal a. Title a general idea of the theme developed in this study is shown; continues to point b. Summarize the main results are discussed in section c. Introduction The importance of the research topic and the contribution that the company provides, in paragraph d detailed. Literature Review concepts that theoretically support the different phases of the classification and valuation of positions was discussed, as well as the rules for admission and employment: the literal e. Materials and methods detailing the materials used and the methods that were used to support development of this work; in subsection f. Results, interviews and surveys provided support for the situational analysis where it was identified in the first instance that the current structure of the company was not for the reality of it, given that the chart reflects 35 posts and are presented true there were 31 jobs, this is because in some cases charges are indicated as the different functions of an employee which appears larger structure of the real. In view of the situation in subsection g. Discussion proceeded to redesign the current chart, first identifying the various departments and function according to the principle of Unity of direction, identifying six departments: production, construction, maintenance, administration and finance, sales and human resources. In addition, to cover certain needs the following changes are proposed, the Chief of Asphalt Plant, the collection was removed by what he termed as billing and collections and added as mechanic. Furthermore it was necessary to appoint heads of each department therefore the respective heads assigned in cases in which there is a charge proceeded to change the designation of positions such as Technical Manager Head of production department was called, the superintendent of maintenance and equipment maintenance chief administrative and financial manager was named head of the administration and finance department was called. While works departments, sales and human resources there is no charge, so that the following posts are created: chief works department, sales department manager, department head of human resources. With the proposed changes and the assignment of responsible EQFALTO organic structure, which is structured with 32 seats was completed. Then the structural, positional and functional charts are developed, defining the hierarchical levels in order to improve internal communication; likewise the manual job classification for the 32 existing positions, where the primary purpose of each position, specific duties, responsibilities, working conditions and minimum requirements described was developed. The job evaluation was conducted to determine their individual value, allowing for a comprehensive judgment through the analysis of the factors and sub-factors, identifying the need for wage adjustment to 25 of the 32 existing positions, the recovery factor is 2,954560907 for each point assigned to different positions, this analysis established just compensation, helping to improve job satisfaction. Then the rules for admission and employment was developed through which the proper procedure for the recruitment, selection, recruitment, induction and training of staff is set. Finally it is recommended to use the proposed proposal, which provides tools to help improve the management of human talent, enabling improved efficiency and staff productivity